Support for the World Bank Soil Health Innovation Challenge - Hauke, Dahl; Peterson, Nathanial Richard (2025)
This report documents AICCRA’s engagement in the World Bank’s Soil Health Innovation Challenge, held in Nairobi in May 2025. It details how AICCRA, through the Alliance of Bioversity International and CIAT, provided scientific, technical, and advisory support to the design, evaluation, and implementation of the Challenge. Using the AICCRA Accelerator Playbook, the team co-developed evaluation criteria, moderated selection panels, and led technical onboarding for nine early-stage ventures in soil testing, biofertilizers, precision agriculture, and soil carbon sequestration. The collaboration showcased how AICCRA strengthens World Bank innovation programs by embedding research-based acceleration, scientific validation, and data-driven evaluation within venture processes. The report underscores AICCRA’s value as a strategic implementation partner capable of linking science, policy, and private enterprise for scalable, climate-smart agricultural innovation